Bodies that matter: Calixthe Beyala’s female bodies and strategies of hegemonic subversion (2018)
Without challenging hegemony, liberal Francophone African feminists unearth aspects of patriarchal African cultural practices that objectify women. In contrast, radical Francophone African feminists call for drastic change to these practices through reappropriating the female body as a way to liberate African women from patriarchal oppression. They challenge the patriarchal order by opposing gender roles and stereotypes and by taking a decisive stand for total female liberation. They call for a radical reordering of patriarchal societies through the annulment of binary oppositions that classify women as “other.” In this article, I follow Judith Butler’s lead in Bodies That Matter: On the Discursive Limits of Sexl and explore Calixthe Beyala’s commitment to African women’s liberation from oppression. Beyala’s approach presents auto-eroticism, homicide, infanticide, refusal of marriage, bodily and psychical dis-eroticization, and physical transformation of female bodies as strategies to secure women’s freedom.